Signs of the times: A review of Mark Hutchinson, Iron in our blood, a history of the Presbyterian Church in NSW, 1788-2001 - B. Zuiddam (Acta Theologica)
From text: The highest praise that can possibly be bestowed upon the author and his book is that the story is so well and accurately told that it need never be written again.